2014
DOI: 10.1007/s12550-014-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone degradation by two Pseudomonas strains from soil

Abstract: This study describes the screening of soil bacteria for their capability to degrade zearalenone (ZEN), employing an enrichment technique in which ZEN is used as the sole carbon source. Two isolates that were able to degrade ZEN belonged to the genus Pseudomonas according to biochemical characterization and 16S rRNA gene sequence and were named as Pseudomonas alcaliphila TH-C1 and Pseudomonas plecoglossicida TH-L1, respectively. The results showed that the degradation rates of P. alcaliphila TH-C1 and P. plecog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…A careful selection of environmental sources more likely to harbor MBMs should increase the probability of finding functional microorganisms. Previous studies have isolated microorganisms from a range of environmental [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29], plant [30,31,32,33,34,35,36,37,38] and animal [39,40,41,42,43,44,45,46,47,48] sources.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A careful selection of environmental sources more likely to harbor MBMs should increase the probability of finding functional microorganisms. Previous studies have isolated microorganisms from a range of environmental [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29], plant [30,31,32,33,34,35,36,37,38] and animal [39,40,41,42,43,44,45,46,47,48] sources.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…It has been reported that DON, ZEA, PAT and CIT can be utilized as a sole carbon source and ultimately biotransformed by a number of microbial strains [13,15,18,23,24,26,27,29,32,41,54]. Due to the high cost and toxicity of many pure mycotoxins, chemically-related compounds may be substituted as the sole carbon source when screening for potential MBMs [25,46,55,56].…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
See 3 more Smart Citations